2003
DOI: 10.1038/sj.cdd.4401131
|View full text |Cite
|
Sign up to set email alerts
|

EGF activates an inducible survival response via the RAS-> Erk-1/2 pathway to counteract interferon-α-mediated apoptosis in epidermoid cancer cells

Abstract: The mechanisms of tumor cell resistance to interferon-a (IFNa) are at present mostly unsolved. We have previously demonstrated that IFNa induces apoptosis on epidermoid cancer cells and EGF antagonizes this effect. We have also found that IFNa-induced apoptosis depends upon activation of the NH 2 -terminal Jun kinase-1 (Jnk-1) and p 38 mitogenactivated protein kinase, and that these effects are also antagonized by EGF. At the same time, IFNa increases the expression and function of the epidermal growth factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 45 publications
7
87
0
Order By: Relevance
“…Survival signalling processes protect against apoptosis induced by specific stimuli [19,21]. Our group and others have demonstrated that some apoptotic stimuli inhibit the Ras → ERK survival signal pathway by decreasing the protein levels of various survival components [21,32].…”
Section: Effects Of Ctn On Components Of Survival Signallingmentioning
confidence: 95%
See 1 more Smart Citation
“…Survival signalling processes protect against apoptosis induced by specific stimuli [19,21]. Our group and others have demonstrated that some apoptotic stimuli inhibit the Ras → ERK survival signal pathway by decreasing the protein levels of various survival components [21,32].…”
Section: Effects Of Ctn On Components Of Survival Signallingmentioning
confidence: 95%
“…In addition, the Ras-regulated ERK activation signal transduction pathway, which includes Raf-1 and MEK, is involved in both proliferation and anti-apoptosis [18]. Ras → ERK-mediated survival signalling has been shown to protect human epidermoid cancer KB cells from various apoptotic inducers [19][20][21]. Together, these previous results suggest that HSP90/multichaperone complex-mediated regulation of apoptotic or survival signal pathway kinases is an efficient mechanism for regulating cell death and survival at the protein level.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that IFNa activates an anti-apoptotic pathway mediated by an EGF-ras-C-RafMek signal transduction pathway. 19 Therefore, it was analyzed if this pathway was responsible for the phosphorylation of eEF-1A. H1355 cells, exposed or not to IFNa, were immunoprecipitated with anti-eEF-1A or anti-C-Raf antibody and blotted with anti-C-Raf or anti-eEF-1A antibody, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that IFNa increased the phosphorylation of both serine and threonine residues in eEF-1A. Because in the same experimental model, IFNa induces an increase in the level and activity of epidermal growth factor receptor (EGF-R) and of the Ras-C-Raf-Mek1-Erk-1/2 signalling pathway that has a prominent role in anti-apoptotic effects, 19 it was evaluated if the phosphorylation of eEF-1A could be mediated by C-Raf. It was found that eEF-1A indeed interacts with CRaf and these effects could be potentiated by IFNa.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation